Research progress and applications of nanobody in human infectious diseases - Mei, Yaxian; Chen, Yuanzhi; Sivaccumar, Jwala P.; An, Zhiqiang; Xia, Ningshao; Luo, Wenxin (Frontiers in Pharmacology, 2022)
Infectious diseases, caused by pathogenic microorganisms, are capable of affecting crises. In addition to persistent infectious diseases such as malaria and dengue fever, the vicious outbreaks of infectious diseases such as Neocon, Ebola and SARS-CoV-2 in recent years have prompted the search for more efficient and convenient means for better diagnosis and treatment. Antibodies have attracted a lot of attention due to their good structural characteristics and applications. Nanobodies are the smallest functional single-domain antibodies known to be able to bind stably to antigens, with the advantages of high stability, high hydrophilicity, and easy expression and modification. They can directly target antigen epitopes or be constructed as multivalent nanobodies or nanobody fusion proteins to exert therapeutic effects. This paper focuses on the construction methods and potential functions of nanobodies, outlines the progress of their research, and highlights their various applications in human infectious diseases.